Extended beta distributions open the access to fast gating in bilayer experiments—assigning the voltage‐dependent gating to the selectivity filter. Issue 23 (19th November 2017) - Rauh, Oliver; Hansen, Ulf‐Peter; Mach, Sebastian; Hartel, Andreas J.W.; Shepard, Kenneth L.; Thiel, Gerhard; Schroeder, Indra
Abstract : Lipid bilayers provide many benefits for ion channel recordings, such as control of membrane composition and transport molecules. However, they suffer from high membrane capacitance limiting the bandwidth and impeding analysis of fast gating. This can be overcome by fitting the deviations of the open‐channel noise from the baseline noise by extended beta distributions. We demonstrate this analysis step‐by‐step by applying it to the example of viral K + channels (Kcv), from the choice of the gating model through the fitting process, validation of the results, and what kinds of results can be obtained. These voltage sensor‐less channels show profoundly voltage‐dependent gating with dwell times in the closed state of about 50 μs. Mutations assign it to the selectivity filter. Abstract :